2012
DOI: 10.1111/j.1439-0272.2012.01316.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome after insemination with donor sperm in patients with poor results in ICSI cycles

Abstract: The introduction of intracytoplasmic sperm injection (ICSI) provided an effective treatment for infertile couples whose infertility was attributed to male factors. However, some of them face poor results after ICSI and subsequently use artificial insemination with donor sperm (AID). Only a few studies have reported on the clinical outcome of AID cycles after previous failed ICSI cycles, with contrasting results. The results reported here involve a cohort of 47 couples undertaking 175 AID cycles after 120 faile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…However, after injection of the vitrified‐warmed sibling oocytes, with frozen‐thawed donor sperms, the pregnancy and live birth were achieved 1 . Similar to this case, when the ejaculated sperms or TESE sample have poor quality or resulted in unsatisfactory clinical outcomes, the use of a third person's sperm is recommended in almost all IVF centers worldwide 13 …”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, after injection of the vitrified‐warmed sibling oocytes, with frozen‐thawed donor sperms, the pregnancy and live birth were achieved 1 . Similar to this case, when the ejaculated sperms or TESE sample have poor quality or resulted in unsatisfactory clinical outcomes, the use of a third person's sperm is recommended in almost all IVF centers worldwide 13 …”
Section: Discussionmentioning
confidence: 57%
“…1 Similar to this case, when the ejaculated sperms or TESE sample have poor quality or resulted in unsatisfactory clinical outcomes, the use of a third person's sperm is recommended in almost all IVF centers worldwide. 13 Assisted reproductive technology therapies are offered to infertile couples in ways shaped by their local considerations, including their social, cultural, religious, economic, ethical, and political circumstances. In this case, we had to inject immotile sperms with a severe morphological abnormality due to the limitation of the use of the donor sperm.…”
Section: Discussionmentioning
confidence: 99%
“…However, some of infertile couples face poor results after ICSI and subsequently use artificial insemination with donor sperm. These couples with a history of unsuccessful ICSI cycles because of poor embryo quality are able to achieve high live birth rate after AID cycles 12 . Ghoraeian et al 13 demonstrated that men especially with severe oligozoospermia have an elevated risk for chromosome abnormalities in their spermatozoa.…”
Section: Discussionmentioning
confidence: 99%